Corporate Governance: The Role of Other Constituencies - Reinhard H. Schmidt (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 1997)
The paper discusses the role of various constituencies in the corporate governance of a corporation from the perspective of incomplete contracts. A strict shareholder value orientation in the sense of a rule that at any time firm decisions should be made strictly in the interest of the present shareholders would make it difficult for the firm to establish long-term relationships as the potential partners would have to fear that, at a later stage of the co-operation, the shareholders or a management acting only on their behalf could exploit them because of the inevitable incompleteness of long-term contracts. One way of mitigating these problems is to put in place a corporate governance system which gives some active role to the other stakeholders or constituencies, or which makes their interests a well-defined element of the objective function of the firm. A commitment not to follow a policy of strict shareholder value maximization ex post can be efficient ex ante. Such a system would clearly differ from what is advocated by proponents of a stakeholder approach, as it would limit the rights of the other constituencies to those which would have been agreed upon in a constitutional contract concluded between them and the founder of the firm at the time when long-term contracts are first established.
urn:nbn:de:hebis:30-16584
Keywords: D21; D23; L21; 330; corporate governance; incomplete contracts; theory of the firm; Corporate Governance; Unternehmensverfassung; Theorie der Unternehmung; Unvollständiger Vertrag; Theorie